Response of gas exchange parameters in Ipomoea batatas under colombian dry caribbean conditions (2018)
Ipomoea batatas L. is one of the crops that has greater importance in the world for its high content of dietary fiber, vitamins and antioxidant compounds; and it is widely known for its consumption in more than 100 countries (García-Méndez et al., 2016). In addition being a source for industrial production of flour, starch and alcohol, the sweet potato is a rustic species, which has great resistance to pets and diseases and is adapted to various tropical areas (Reina,2015). Its rusticity also implies the requirement of lower doses of fertilizers, such as N and P, and lower quantity of pesticides. The sweet potato is considered one f the most efficient species in the use of water; so it could be grown on soils with marginal agricultural value (La Rosa,2008).